The impact of KLF2 modulation on the transcriptional program and function of CD8 T cells. - Gavin C Preston; Carmen Feijoo-Carnero; Nick Schurch; Victoria H Cowling; Doreen A Cantrell (PLoS ONE)
Krüppel-like factor 2 (KLF2) is a transcription factor that is highly expressed in quiescent T lymphocytes and downregulated in effector T cells. We now show that antigen receptor engagement downregulates KLF2 expression in a graded response determined by the affinity of T cell antigen receptor (TCR) ligand and the integrated activation of protein kinase B and the MAP kinases ERK1/2. The present study explores the importance of KLF2 downregulation and reveals that the loss of KLF2 controls a select portion of the CD8 effector T cell transcriptional program. In particular, KLF2 loss is required for CD8 T cells to express the inflammatory chemokine receptor CXCR3 and for maximum clonal expansion of T cells. KLF2 thus negatively controls the ability of CD8 T cells to respond to the CXCR3 ligand CXCL10. Strikingly, the KLF2 threshold for restraining expression of CXCR3 is very low and quite distinct to the KLF2 threshold for restraining T cell proliferation. KLF2 is thus an analogue (tunable) not a digital (on/off) cellular switch where the magnitude of KLF2 expression differentially modifies the T cell responses.